PENGARUH CURRENT RATIO DAN REVENUE GROWTH TERHADAP NET PROFIT MARGIN PADA PT ADHI KARYA PERSERO TBK PERIODE 2013 – 2023 - Sundari Putri, Ayu; Muhammad Lutfi, Asep (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Current Ratio and Revenue Growth on Net Profit Margin  partially and simultaneously. The method used in this research is a quantitative approach.  The population used in this study is the annual financial report. The sample used is the balance sheet and profit and loss. The data analysis technique used is descriptive analysis and statistical analysis through the SPSS calculation stage using IBM SPSS version 25. From the research results it is known that the t value is 3.026> t table 2.26216 with a significant level of 0.016 <0.05, meaning that partially there is an influence between the Current Ratio variable on Net Profit Margin. From the second test results, it is known that the value of t count -1.766 < t table 2.26216 with a significant level of 0.115> 0.005 means that partially there is no influence between the Revenue Growth variable on Net Profit Margin. It is known that the value of change sig. F 0.028 <0.05, it is concluded that simultaneously Current Ratio and Revenue Growth have a significant effect on Net Profit Margin.